Tetraaquabis(isonicotinamide-κN (1))cobalt(II) bis(4-formylbenzoate) dihydrate - Hökelek, Tuncer (International Union of Crystallography, 2009)
The asymmetric unit of the crystal structure of the title complex, [Co(C(6)H(6)N(2)O)(2)(H(2)O)(4)](C(8)H(5)O(3))(2)·2H(2)O, contains one-half of the complex cation with the Co(II) ion located on an inversion center, a 4-formylbenzoate (FB) counter-anion and an uncoordinated water molecule. The four O atoms in the equatorial plane around the Co(II) ion form a slightly distorted square-planar arrangement with an average Co—O bond length of 2.086 Å; the slightly distorted octahedral coordination is completed by the two N atoms of the isonicotinamide (INA) ligands at a slightly longer distance [2.1603 (14) Å] in the axial positions. The dihedral angle between the carboxylate group and the attached benzene ring is 5.93 (13)°, while the pyridine and benzene rings are oriented at a dihedral angle of 3.09 (6)°. In the crystal structure, O—H⋯O, N—H⋯O and C—H⋯O hydrogen bonds link the molecules into a three-dimensional network. π–π Contacts between the benzene and pyridine rings [centroid–centroid distance = 3.758 (1) Å] may further stabilize the crystal structure.